Gastric Bypass Surgery Is Followed by Lowered Blood Pressure and Increased Diuresis - Long Term Results from the Swedish Obese Subjects (SOS) Study - Hallersund, Peter; Sjöström, Lars; Olbers, Torsten; Lönroth, Hans; Jacobson, Peter; Wallenius, Ville; Näslund, Ingmar; Carlsson, Lena M.; Fändriks, Lars (PloS one, 2012)
To compare two bariatric surgical principles with regard to effects on blood pressure and salt intake. In most patients bariatric surgery induces a sustained weight loss and a reduced cardiovascular risk profile but the long-term effect on blood pressure is uncertain. Cohort study with data from the prospective, controlled Swedish Obese Subjects (SOS) study involving 480 primary health care centres and 25 surgical departments in Sweden. Obese patients treated with non-surgical methods (Controls, n = 1636 and n = 1132 at 2 y and 10 y follow up, respectively) were compared to patients treated with gastric bypass (GBP, n = 245 and n = 277, respectively) or purely restrictive procedures (vertical banded gastroplasty or gastric banding; VBG/B, n = 1534 and n = 1064, respectively). At long-term follow-up (median 10 y) GBP was associated with lowered systolic (mean: -5.1 mm Hg) and diastolic pressure (-5.6 mmHg) differing significantly from both VBG/B (-1.5 and -2.1 mmHg, respectively; p<0.001) and Controls (+1.2 and -3.8 mmHg, respectively; p<0.01). Diurnal urinary output was +100 ml (P<0.05) and +170 ml (P<0.001) higher in GBP subjects than in weight-loss matched VBG/B subjects at the 2 y and 10 y follow-ups, respectively. Urinary output was linearly associated with blood pressure only after GBP and these patients consumed approximately 1 g salt per day more at the follow-ups than did VBG/B (P<0.01). The purely restrictive techniques VBG/B exerted a transient blood pressure lowering effect, whereas gastric bypass was associated with a sustained blood pressure reduction and an increased diuresis. The daily salt consumption was higher after gastric bypass than after restrictive bariatric surgery.